Evaluación de la acumulación de grados día desarrollo (GDD) sobre cinco estados fenológicos del cultivo de la VID (Vitis Vinífera Var. Verdejo) en tres pisos altitudinales bajo dos niveles de fertilización - Cháfuel Gallegos, Javier Eduardo (2024)
Grape cultivation in Ecuador began in the 1970s, and the first plantations were carried out in 1983. Currently, the area planted with grapes reaches 250 hectares, according to the records of the Ministry of Agriculture. The objective of this study is to evaluate the accumulation of Development Degree Days (GDD) over five phenological states of grapevine cultivation (Vitis vinifera var. Verdejo) in three altitudinal levels under two fertilization levels. The field trial was carried out in the towns of Cotacachi, Ibarra and El Ángel, with a duration of 100 days. A bifactor design was applied that included two factors: grape variety and altitude, with two levels of fertilization, thus obtaining 6 treatments and 4 repetitions. A total of 24 experimental units were used, represented by 3 Verdejo grape plants under greenhouse conditions. The variables evaluated included the maximum and minimum temperature, the duration in days of each phenological stage and the number of clusters per treatment. Data analysis was carried out using Infostat software. The accumulation of Degree Days Development for the altitudes of Cotacachi, Ibarra and El Ángel was 1025.98 GDD, 985 GDD, and 947 GDD\; respectively. The lowest number of days in grape production was recorded in the town of Ibarra, with 75 days, while in El Ángel and Cotacachi it represented 99 and 89 days, respectively. The largest number of clusters, 16 clusters per plant, was observed in the town of Ibarra under a chemical treatment.